Hybrid study of digital entrepreneurship in the COVID-19 era - Rincón Ornelas, Rosa María; Zallas Esquer, Lidia Amalia; Sanchez Sanchez, Arturo; García Lirios, Cruz; Chaparro Medina, Jorge E.; Rincòn Rodrìguez, Isabel Cristina (Journal of Sustainable Economics, 2023)
The objective of this work was to specify a model for the study of electronic consumption. An exploratory, cross-sectional and psychometric study was conducted with a selection of Internet users, considering their time of use. An associative perceptual structure was found between the usefulness of the technology and the effectiveness of the respondent, although the research design limited the results to the research sample, suggesting the extension of the work towards other cybernetic contexts.